Encouraging self-regulated learning: examining the feedback approaches and teaching strategies employed by English Home Language teachers - Manuel, Jesmien; Geduld, Bernadette; Kaiser, Kotie (Frontiers in Education, 2024)
The additive approach to multilingualism followed in South African public schools complicate teaching and learning in English Home Language. Many non-native speaking learners underperform since they must learn in an unfamiliar language, which differs from theirs socially and culturally. Throughout the teaching and learning process, learners encounter diverse language challenges. Consequently, teachers play a crucial role in aiding learners to surmount these hurdles by offering both sufficient and effective feedback. Proficient feedback practices have the potential to bolster the self-regulation capabilities of non-native speakers and underperforming learners, thereby preparing them for a lifetime of learning. The aim of this study was to investigate the predominant types and levels of feedback utilized in the classrooms of intermediate phase teachers within English Home Language education, as well as how this feedback is employed to promote the development of learners’ self-regulated learning skills. The empirical study was approached by means of a qualitative research design in the form of an instrumental case study. Observations and individual, semi-structured interviews were used to collect data from 15 purposively selected teachers from five different schools in the Ennerdale region in Gauteng, South Africa. The findings indicate that while there is some promotion of self-regulated learning skills, discrepancies exist between participants’ perceptions of how their feedback practices foster these skills, as revealed in interview data, and their actual teaching methods. Participants predominantly employ traditional, transmission-based teaching approaches, demonstrating limited comprehension of the diverse self-regulated skills that could enhance academic achievement, particularly in English Home Language. Moreover, there is a deficiency in pedagogical knowledge regarding the application of these skills within their teaching practices. These findings suggest a misalignment between teachers’ perceptions of their feedback practices and the actual implementation of these practices in promoting self-regulated learning skills among students in English Home Language education. The predominance of traditional teaching approaches and limited understanding of self-regulated learning skills among teachers highlight potential barriers to the effective cultivation of these skills in the classroom. This misalignment is significant as it indicates a gap between teachers’ intentions and their instructional practices, which can hinder students’ ability to develop essential self-regulated learning skills necessary for academic success. Furthermore, the deficiency in pedagogical knowledge regarding the application of these skills underscores the need for targeted professional development initiatives to support teachers in integrating effective feedback practices that promote self-regulated learning. Overall, these findings underscore the importance of aligning teachers’ perceptions and practices with the promotion of self-regulated learning skills, particularly in the context of English Home Language education. Addressing these discrepancies through targeted interventions and professional development can ultimately enhance students’ academic achievement and overall learning outcomes.